Formation of Evolved Rocks at Gale Crater by Crystal Fractionation and Implications for Mars Crustal Composition. Issue 6 (22nd June 2018) - Udry, Arya; Gazel, Esteban; McSween, Harry Y.
Abstract: The recent discovery of some ancient evolved rocks in Gale crater by the Curiosity rover has prompted the hypothesis that continental crust formed in early Martian history. Here we present petrological modeling that attempts to explain this lithological diversity by magma fractionation. Using the thermodynamical software MELTS, we model fractional crystallization of different Martian starting compositions that might generate felsic igneous compositions like those analyzed at Gale crater using different variables, such as pressure, oxygen fugacities, and water content. We show that similar chemical and mineralogical compositions observed in Gale crater felsic rocks can readily be obtained through different degrees of fractional crystallization of basaltic compositions measured on the Martian surface. The results suggest that Gale crater rocks may not represent true liquids as they possibly accumulated and/or fractionated feldspars as well as other phases. In terms of major element compositions and mineralogy, we found that the Gale crater felsic compositions are more similar to fractionated magmas produced in Earth's intraplate volcanoes than to terrestrial felsic continental crust as represented by tonalite‐trondhjemite‐granodiorite suites. We conclude that the felsic rocks in Gale crater do not represent continental crust, as it is defined on Earth. Key Points: Recent in situ data changed our understanding of the crustal composition of Mars Alkaline and felsic rocks can also be reproduced through different degrees of fractional crystallization Continental crust, as defined by large amounts of quartz‐bearing felsic rocks, is unique to Earth